An uncommon case of neonatal asphyxia associated with infantile-onset Pompe disease - Francesco Leo; Luca Barchi; Giulia Russo; Eleonora Balestri; Elena Chesi; Francesco Di Dio; Livia Garavelli; Lorenzo Iughetti; Giancarlo Gargano (Italian Journal of Pediatrics)
Abstract Background Pompe disease, also known as glycogenosis type II or acid maltase deficiency, is an autosomal recessive disease caused by a deficiency of alpha-glucosidase. The severity depends mainly on the type of mutation, which in turn determines early or late onset; therapy modifies the outcome but does not alter the severity of the disease at presentation. Case presentation We present a case report of a male infant, inborn and delivered at a gestational age of 39 weeks. Medical history reveals consanguineous parents with no invasive screening tests performed during pregnancy. They chose not to undergo prenatal screening even though they were aware of the risks associated with their consanguinity. At birth, the newborn was atonic and pale, with a heart rate of 70 bpm. During resuscitation, an umbilical venous catheter was placed, and three doses of adrenaline and one dose of bicarbonate were administered. At the Neonatal Intensive Care Unit, he underwent therapeutic hypothermia. Echocardiography, performed a few hours later, revealed severe biventricular and septal hypertrophy consistent with non-obstructive hypertrophic cardiomyopathy. During recovery, even after the discontinuation of hypothermia, the newborn exhibited abnormal neurological signs, including axial hypotonia and a tendency to keep his mouth open with tongue protrusion. Given the clinical picture and the early detection of septal and biventricular hypertrophy, genetic testing was performed, revealing a homozygous c.2560 C > T variant in the acid alpha-glucosidase gene (both parents were carriers), described in scientific literature as a class 5 pathogenic variant associated with glycogenosis type II (Pompe disease). Conclusion Pompe disease is a rare genetic disorder and may be difficult to diagnose at birth. Suspicion should arise in the presence of hypertrophic cardiomyopathy, especially when associated with a history of neonatal asphyxia and abnormal neurological signs. An accurate diagnosis and early treatment are essential to improving the patient’s survival and quality of life.